Health conditions and unmet needs for assistance to perform activities of daily living among older adults with dementia in Chile. (23rd March 2018) - Zhou, Yi; Slachevasky, Andrea; Calvo, Esteban
Abstract : Objective: This study aims to address gaps in health conditions and unmet needs in daily activities between people with dementia (PWD) and without dementia in a developing country and to identify the variables associated with unmet needs among PWD to guide practitioners and policymakers in dealing with an increased burden of dementia. Methods: Nationally representative data on 4655 Chileans age 60 and over were used to compare health conditions and unmet needs in daily life activities between individuals with (N = 455, 9.6%) and without dementia. Regression analysis was conducted to identify the variables associated with unmet needs among PWD. Results: Overall, PWD had worse health and needed greater assistance in performing daily activities than people without dementia. Among PWD, being male was associated with more unmet needs, in both activities of daily living (ADL) and instrumental ADL. Lower educational level and fewer caregivers were associated with more unmet needs for ADL, while inferior functional ability was associated with more unmet needs for instrumental ADL. Conclusions: The results from this study call for action by practitioners and policymakers to foster caregiver training, increase supportive services, and advance care planning for PWD.